Facile synthesis of three-dimensional conducting scaffold with magnesiophilic decorations toward non-dendritic Mg-metal batteries - KWAK, JIN HWAN; Sunghee, Shin; Yunseo Jeoun; Lee, Yongheum; Yu, Seung ho; Young Soo Yun; Yung-Eun Sung; Seung-Ho Yu; Lim, Hee Dae (Elsevier BV, 2022)
Despite the substantial efforts aimed at suppressing metallic dendrite growth in Li-metal batteries, Mg-metal dendrite growth has thus far received relatively little attention, and the formation of Mg dendrites has recently been shown to be a critical limitation for the practical advancement of rechargeable Mg-ion batteries. The development of an appropriate anode to efficiently accommodate Mg deposits is thus key to overcome this limitation. Here, we report the unique design of Ag-decorated Cu foam (ACF) consisting of a porous Cu scaffold decorated with magnesiophilic Ag nanoparticles (NPs) on its surface through a facile one-step synthesis process. For the first time, we demonstrate the strong affinity of Ag atoms to the electrochemically deposited Mg; magnesiophilicity is then adopted to design an efficient anode host for Mg-metal batteries and suppress the Mg dendritic formation. As a result, the ACF exhibits a greatly decreased nucleation overpotential with a longer cycle life compared with those of conventional substrates. In the absence of magnesiophilic Ag nano-seeds, non-uniform and top-oriented Mg depositions are observed; in contrast, the ACF helps contribute to an even deposition of the electrochemically formed Mg over the entire active surface, resulting in improved electrochemical performance.